The methyltransferase G9a regulates HoxA9-dependent transcription in AML - Lehnertz, Bernhard; Pabst, Caroline; Su, Le; Miller, Michelle; Liu, Feng; Yi, Lin; Zhang, Regan; Krosl, Jana; Yung, Eric; Kirschner, Jeanette; Rosten, Patty; Underhill, T Michael; et al. (Genes & development, 2014)
histone methylation, hematopoiesis, leukemia, Hox genes